Variations in fatty acid composition, glucosinolate profile and some phytochemical contents in selected oil seed rape (Brassica napus L.) cultivars - El-Din Saad El-Beltagi, Hossam; Amin Mohamed, Amal (Grasas y Aceites, 2010)
Rapeseed (Brassica napus L.) is now the third most important source of edible oil in the world after soybean and palm oil. In this study seeds of five different rapeseed cultivars namely; pactol, silvo, topas, serw 4 and serw 6 were evaluated for their fatty acid composition, glucosinolate profile, amino acids, total tocopherols and phenolic content. Among all cultivars significant variability in fatty acids were observed. The oleic acid (C18:1) ranged from 56.31% to 58.67%, linoleic acid (C18:2) from 10.52% to 13.74%, α-linolenic acid (C18:3) from 8.83% to 10.32% and erucic acid (22:1) from 0.15% to 0.91%. The glucosinolate profile of rapeseed was also separated and identified using high-performance liquid chromatography. Small variations in the glucosinolate profile were observed among all tested cultivars; however, progoitrin and gluconapin were the major glucosinolate found. Additionally, silvo cultivar showed the highest total glucosinolate c ontents (5.97 μmol/g dw). Generally, the contents of aspartic, glutamic, arginine and leucine were high, while the contents of tyrosine and isoleucine were low among all cultivars. For total tocopherols, the results indicated that both serw 6 and pactol cultivars had the highest total tocopherol contents (138.3 and 102.8 mg/100 g oil, respectively). Total phenolic contents varied from 28.0 to 35.4 mg/g dw. The highest total phenolic content was found in topas while the lowest value was detected in serw 6. These parameters; fatty acid contents, glucosinolate profile and amino acids together with total tocopherols and phenolic contents, could be taken into consideration by oilseed rape breeders as selection criteria for developing genotypes with modified seed quality traits in Brassica napus L.